Demonstrating ignition hydrodynamic equivalence in direct-drive cryogenic implosions on OMEGA. (May 2016) - Goncharov, V N; Regan, S P; Sangster, T C; Betti, R; Boehly, T R; Campbell, E M; Delettrez, J A; Edgell, D H; Epstein, R; Forrest, C J; Froula, D H; Glebov, V Yu; et al.
Abstract: Achieving ignition in a direct-drive cryogenic implosion at the National Ignition Facility (NIF) requires reaching central stagnation pressures in excess of 100 Gbar, which is a factor of 3 to 4 less than what is required for indirect-drive designs. The OMEGA Laser System is used to study the physics of cryogenic implosions that are hydrodynamically equivalent to the spherical ignition designs of the NIF. Current cryogenic implosions on OMEGA have reached 56 Gbar, and implosions with shell convergence CR< 17 and fuel adiabat α > 3.5 proceed close to 1-D predictions. Demonstrating hydrodynamic equivalence on OMEGA will require reducing coupling losses caused by cross-beam energy transfer (CBET), minimizing long- wavelength nonuniformity seeded by power imbalance and target offset, and removing target debris occumulated during cryogenic target production.